Hyperglycaemia and Risk of Adverse Perinatal Outcomes: Systematic Review and Meta-analysis. Issue 2 (June 2017) - Farrar, D.; Simmonds, M.; Bryant, M.; Sheldon, T.A.; Tuffnell, D.; Golder, S.; Dunne, F.; Lawlor, D.A.
Abstract : ( BMJ . 2016;354:i4694) Gestational diabetes increases the risk for some adverse perinatal outcomes such as macrosomia and cesarean section. However, uncertainty exists regarding the most appropriate glucose threshold at oral glucose tolerance testing (OGTT) to define gestational diabetes. The present study aimed to evaluate the association between maternal glucose concentrations and adverse perinatal outcomes in women without gestational diabetes or preexisting diabetes, and to determine whether there are obvious evidence-based glucose thresholds that can identify women at increased risk of adverse perinatal outcomes.